Emotional Intelligence, Cognitive Intelligence, and Job Performance - Côté, Stéphane; Miners, Christopher T. H. (Administrative Science Quarterly, 2006)
This paper examines how emotional intelligence and cognitive intelligence are associated with job performance. We develop and test a compensatory model that posits that the association between emotional intelligence and job performance becomes more positive as cognitive intelligence decreases. We report the results of a study in which employees completed tests of emotional intelligence and cognitive intelligence, and their task performance and organizational citizenship behavior were assessed by their supervisors. Hypotheses from the model were supported for task performance and organizational citizenship behavior directed at the organization, but not for organizational citizenship behavior directed at individuals. We discuss the theoretical implications and managerial ramifications of our model and findings.